A new record of the Mudskipper Parapocryptes serperaster (Oxudercinae: Gobiidae) from peninsular Malaysia. - Khaironizam, M.Z.; Norma-Rashid, Yusoff (Faculty of Science, University of Malaya, 2000)
Species of the gobiid fishes that are commonly known as musskippers abound on the mudflas of Selangor coasts. The material examined is deposited at the Institute of Biological Sciences, University of Malaya and identified by using the key of Koumans and Murdy. One of the specimen of mudskipper Parapocryptes serperaster, a new record for Peninsular Malaysia was captured at Sungai Sembilang, Jeram, Selangor. Its morphological features and habitat utilization are discussed. The preliminary feeding habit is described based on their gu contents.